2003
DOI: 10.1901/jaba.2003.36-253
|View full text |Cite
|
Sign up to set email alerts
|

Using Video Modeling and Reinforcement to Teach Perspective‐taking Skills to Children With Autism

Abstract: We evaluated video modeling and reinforcement for teaching perspective-taking skills to 3 children with autism using a multiple baseline design. Video modeling and reinforcement were effective; however, only 2 children were able to pass an untrained task, indicating limited generalization. The findings suggest that video modeling may be an effective technology for teaching perspective taking if researchers can continue to develop strategies for enhancing the generalization of these new skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
132
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(139 citation statements)
references
References 5 publications
1
132
1
5
Order By: Relevance
“…Baron-Cohen et al (1985) found that children with autism showed considerable difficulties with the task, whereas typically developing children and children with Down syndrome could easily answer the experimenter's questions about the Sally doll's perspective (the reader is also referred to Baren-Cohen, 1989). LeBlanc, Coates, Daneshvar, Charlop-Christy, Morris, & Lancaster (2003) similarly found that children with autism were strikingly deficient in their performance on a version of the Sally Anne task. The children weire only able to pass the task after intensive behavioral intervention involving video modeling and positive reinforcement, and even then, the children's generalization of perspective-taking skills to new situations was limited.…”
mentioning
confidence: 87%
“…Baron-Cohen et al (1985) found that children with autism showed considerable difficulties with the task, whereas typically developing children and children with Down syndrome could easily answer the experimenter's questions about the Sally doll's perspective (the reader is also referred to Baren-Cohen, 1989). LeBlanc, Coates, Daneshvar, Charlop-Christy, Morris, & Lancaster (2003) similarly found that children with autism were strikingly deficient in their performance on a version of the Sally Anne task. The children weire only able to pass the task after intensive behavioral intervention involving video modeling and positive reinforcement, and even then, the children's generalization of perspective-taking skills to new situations was limited.…”
mentioning
confidence: 87%
“…(BaronCohen, 2001, p. 174) What makes such definitions problematic for behavior analysts is that ToM researchers almost never identify what children actually do and the circumstances under which they do it, a tack not likely to pique the interest of theorists interested in "tapping children's conception of mind" or understanding "that the mind is a representational system, which does not simply reflect reality" (Hale & Tager-Flusberg, 2003, p. 346). Unfortunately, however, only a handful of behavior analysts have addressed the topic of ToM (e.g., Layng, 2005;LeBlanc et al, 2003;McHugh, Barnes-Holmes, & BarnesHolmes, 2006;McHugh, Barnes-Holmes, Barnes-Holmes, & Stewart, 2004;Okuda & Inoue, 2000;Salzinger, 2006;Schlinger, 2006Schlinger, , 2007Spradlin & Brady, 2008). Because even fewer behavior analysts have experimentally investigated behaviors related to ToM, we are forced to mine the standard developmental literature for studies that support a general behavior-analytic account of ToM.…”
Section: Tom In Humansmentioning
confidence: 99%
“…For example, using a multiple-baseline design across tasks, LeBlanc et al (2003) taught perspective taking to three children with autism using video modeling and reinforcement. The researchers presented two tasks to the children, a false or unexpected-identity task and a hide-andseek task.…”
Section: Tom and Verbal Behaviormentioning
confidence: 99%
See 2 more Smart Citations